2018
DOI: 10.1021/acs.joc.8b02885
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Modular Amino Oxygenation of Alkenes: Access to Diverse 1,2-Amino Oxygen-Containing Skeletons

Abstract: Copper-catalyzed alkene amino oxygenation reactions using O-acylhydroxylamines have been achieved for a rapid and modular access to diverse 1,2-amino oxygen-containing molecules. This transformation is applicable to the use of alcohols, carbonyls, oximes and thio-carboxylic acids as nucleophiles on both terminal and internal alkenes. Mild reaction conditions tolerate a wide range of functional groups, including ether, ester, amide, carbamate, and halide. The reaction protocol allows for starting with free amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…In 2019 Wang and co‐workers reported a copper‐catalyzed modular amino oxygenation of alkenes which gives access to diverse 1,2‐amino oxygen‐containing skeletons [44] . Within this body of work, it was shown that the methodology could be extended towards the synthesis of a γ‐thiolactone (Scheme 13).…”
Section: Intramolecular Radical Routes For Thiolactone Synthesismentioning
confidence: 99%
“…In 2019 Wang and co‐workers reported a copper‐catalyzed modular amino oxygenation of alkenes which gives access to diverse 1,2‐amino oxygen‐containing skeletons [44] . Within this body of work, it was shown that the methodology could be extended towards the synthesis of a γ‐thiolactone (Scheme 13).…”
Section: Intramolecular Radical Routes For Thiolactone Synthesismentioning
confidence: 99%
“…Encouraged by this result, O ‐BHA 1 and BPO 2 were chosen as representative reactants for further optimization of the reaction. In the presence of triethyl phosphite in DCE at 60 °C, reductively dealkylated 2° amide 3 was indeed obtained in 62 % yield, along with benzaldehyde (44 %) and benzoic acid (90 %) as side products (Table , entry 1).…”
Section: Figurementioning
confidence: 99%
“…In this work, we have developed a copper-catalyzed three-component 1,2-amino oxygenation reaction of 1,3-dienes, using O -acyl hydroxylamines as the electrophilic nitrogen source and carboxylic acids as the nucleophilic oxygen source (Scheme 1C). The transformation is envisioned to be initiated by a copper-catalyzed amination of dienes with electrophilic O -acyl hydroxylamines 10 followed by the nucleophilic addition of carboxylic acids. Such amination/oxygenation pathways are distinctly different from previous 1,3-diene methods and thus would allow for a chemo-, regio- and site-selective addition to 1,3-dienes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these amino oxygenation conditions show remarkable selectivity toward 1,3-dienes over non-conjugated olefins, which are also known to undergo similar amino oxygenation reactions. 10 This method also tolerates a diverse scope of carboxylic acids, even those that contain sensitive functional groups. Studies on the reaction pathways offer further mechanistic insights on the radical intermediates and pathways under reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation